678 Kimyo va kimyoviy texnologiyalar: Synthesis of a Non-Isocyanate Urethane Oligomer Based on Phthalic Anhydride - Yusupov, Muzafar; Djalilov, Abdulakhat; Kiyomov, Sharifjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. The purpose of this work is to study the method of synthesizing an oligomer containing urethane groups without the isocyanate method, as well as to conduct an infrared spectroscopic analysis to determine the formed chemical bonds and functional groups in the resulting urethane oligomer. The influence of the temperature of the reaction mass and the reaction time on the average molecular weight of the resulting urethane oligomer is shown. The optimal temperature-time parameters for carrying out the synthesis process without an isocyanate urethane oligomer have been established. Methods. To achieve the goal of this study, a method was used to determine the formed chemical bonds and functional groups. Ethylene glycol, urea, formaldehyde, and phthalic anhydride were used to synthesize the urethane oligomer. The urethane oligomer was obtained by the chemical reaction of polycondensation under vacuum. To determine the optimal temperature and time of the polycondensation reaction, samples were selected that differ in the duration of the reaction, as well as in the temperature of the reaction system. The molecular weights of the samples were determined by cryoscopy. A graph of the dependence of the molecular masses of the samples on the duration of the polycondensation reaction at different temperatures was plotted. Results. The results of the experiments showed that an absorption band in the region of 1640.55 cm-1 was found in the IR spectrum, explaining the presence of the -CO-NH2 group and an absorption band in the region of 1732.08 cm-1, proving the presence of an unsubstituted urethane group.The study of the molecular weight of the obtained urethane oligomer by the cryoscopic method showed that the molecular weight of the oligourethane reaches 3921. The optimal temperature-time condition for the synthesis of this oligourethane is a chemical reaction at 160 ° C and for 120 minutes. Conclusion. The results obtained from the study of the urethane oligomer synthesis method without the isocyanate method indicate that the optimal condition for obtaining a urethane oligomer based on phthalic anhydride is the polycondensation reaction for 120 minutes at a temperature of 160 °C. this method allows to obtain without isocyanate urethane oligomer based on ethylene glycol, urea, formaldehyde and phthalic anhydride, with an average molecular weight reaching 3921.